1996
DOI: 10.1172/jci118909
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of manganese superoxide dismutase against adriamycin-induced acute cardiac toxicity in transgenic mice.

Abstract: Adriamycin (ADR) is a potent anticancer drug known to cause severe cardiac toxicity. Although ADR generates free radicals, the role of free radicals in the development of cardiac toxicity and the intracellular target for ADR-induced cardiac toxicity are still not well understood. We produced three transgenic mice lines expressing increased levels of human manganese superoxide dismutase (MnSOD), a mitochondrial enzyme, as an animal model to investigate the role of ADR-mediated free radical generation in mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
255
4
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(279 citation statements)
references
References 42 publications
15
255
4
2
Order By: Relevance
“…Ultrastructural injury in cardiac tissues was evaluated by electron microscopic analysis on four mice from each treatment groups, using methods described by Yen et al [33] with minor modifications. Heart tissue was cut into 1 mm 3 pieces and fixed in fullstrength Karnovsky′s fixative [4% paraformaldehyde and 5% glutaraldehyde in 0.1 mol/L sodium phosphate buffer (pH 7.4)] for 4 to 5 hours, and then postfixed in Caulfield′s osmium tetroxide with sucrose for 30 to 60 minutes at 4°C.…”
Section: Ultrastructural Examination Of Cardiac Tissuesmentioning
confidence: 99%
“…Ultrastructural injury in cardiac tissues was evaluated by electron microscopic analysis on four mice from each treatment groups, using methods described by Yen et al [33] with minor modifications. Heart tissue was cut into 1 mm 3 pieces and fixed in fullstrength Karnovsky′s fixative [4% paraformaldehyde and 5% glutaraldehyde in 0.1 mol/L sodium phosphate buffer (pH 7.4)] for 4 to 5 hours, and then postfixed in Caulfield′s osmium tetroxide with sucrose for 30 to 60 minutes at 4°C.…”
Section: Ultrastructural Examination Of Cardiac Tissuesmentioning
confidence: 99%
“…Previous experiments, showed that only high level of Mn-sod protected against LDH and CK increase in the serum of transgenic mice. 16 Also complete protection was only obtained with a 10-fold increase in CuZn-sod in transgenic mice 32 while less than five-fold increase in sod activity did not fully protect against free radicals produced by doxorubicin 17 or hypoxia/reoxygenation. 14 MonoHER is a semisynthetic flavonoid.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Indeed, when Mn-sod was endogenously expressed in high levels in transgenic mice a partial protection against doxorubicin-induced cardiotoxicity could be achieved. 16,17 This incomplete protection might be the result of the confinement of Mn-sod to the mitochondria or of the possibility that the levels of Mnsod are still insufficient to show the desired cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not yet clear exactly what mechanism was responsible for either the cardioprotective effects or the over-expression of GAPDH observed 18 in the DOC -ADR group. Previous r esearch ha s s hown t hat the over-expression of antioxidant e nzymes (i.e., superoxide d ismutase and c atalase) in TG mice protected heart from A DR-induced cardiotoxicity [ 58,59]. Therefore, the s ame transgenic approach or another approach with the addition of N 6 -naphthalenemethyl-2'-methoxybenzamido-β-NAD + for GAPDH inhibition [60] may be useful in validating and elucidating any cardioprotective effects associated with GAPDH.…”
Section: Evidence H As Accumulated I Ndicating a Relationship B Etweementioning
confidence: 99%